INTEGRATION OF AI MODULES INTO ONBOARDING PROCESSES: METHODOLOGY AND IMPLEMENTATION RESULTS IN A POLISH HR AGENCY - Gryn, Viacheslav (European Journal of Interdisciplinary Issues, 2025)
This study explores the integration of AI modules into employee onboarding processes, focusing on methodology and implementation outcomes within a Polish HR agency context. In response to rapid digitalization and evolving labor market demands, traditional onboarding methods have become less effective, prompting the adoption of AI-driven solutions to optimize adaptation time, reduce costs, and enhance employee engagement. Through a mixed qualitative and quantitative analysis of leading Polish companies such as Agata S.A., Sagiton Sp. z o.o., Nais Solutions, and international players like Miquido, this research demonstrates significant improvements in onboarding efficiency. Key AI functionalities include automated document management, personalized training content delivery, real-time progress monitoring, AI-assisted candidate screening, and interactive AI chatbots providing continuous employee support. Results indicate onboarding time reduction by up to 60%, cost savings exceeding PLN 250,000, and a 50% increase in new hire activation levels. The study underscores the critical role of a comprehensive implementation approach involving initial audits, AI tool customization, HR personnel training, pilot testing, and scaling, alongside adherence to ethical standards in data processing. These findings offer practical insights for HR agencies aiming to leverage AI technologies to boost competitiveness and employee retention in dynamic labor markets.